Van Gogh's twin the Scottish art dealer Alexander Reid 1854 - 1928 - Fowle, Frances (National Galleries of Scotland, 2010)
Alexander Reid was one of the most influential art dealers of his time. A close friend of Whistler and the Van Gogh brothers, he was the first Brittish dealer to take a serious interest in impressionist art. He was also a contemporary of the Glasgow boys and supported emerging artists such as Henry, Hornel and Crawhall as well as the Scottish colourist. His clients were rich Scottish merchants and industrialists who made their fortunes on the back of Scotland's rapid economic development, and whom he persuaded to buy impressionism well in advance of their English contemporaries. In this first biography devoted to an unsung hero of the Brittish art world, Frances Fowle traces the history of Reid's gallery against the background of a fascinating period of economic boom and bust